SPEECH ACTS USED BY JO MARCH IN MOVIE “LITTLE WOMEN 2019” - istihayyu buansari; Fitri Apriyanti; Indri Diniarti (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This research studies the speech acts of Jo March the main character in the movie Little Women 2019 and aims to find out the type and form of speech acts in Jo's utterances and which one is the most dominant. The speech act is a theory that examines the meaning of language based on the relationship between utterances and actions performed by speakers and hearers to communicate something. This research uses a qualitative descriptive method to obtain data. The writer collected data by watching the movie of Little Women 2019. In investigating Jo's speech acts, this study applied Searle's (1979) theory of speech acts in analyzing the utterances produced by Jo in the movie Little Women. There are five types of speech acts used by Jo, including assertive with 5 utterances, directive with 10 utterances, commissive with 6 expressive utterances with 9 utterances, and declarative with 2 utterances. So, the amount of data is 32 data and the most dominant speech act used by Jo is the directive speech act.